A review on knowledge of diabetes and practice of medication adherence among people living with diabetes mellitus - Nurumal, Mohd. Said; Jamaludin, Thandar Soe Sumaiyah; Mohammad, Nurfatihah Masrurah; Che Hasan, Muhammad Kamil; Win, Kyu Kyu (IIUM Press, 2020)
Introduction: The prevalence of diabetes among adults is increasing globally in the 21st century. However, the knowledge of diabetes and practice of medication adherence among people living with diabetes mellitus are still questionable. Aims: This literature review aimed to look for the literature that related to the level of knowledge about diabetes and its correlation with medication adherence among people living with diabetes mellitus. Methods: The studies included in this review were identified through a search of Proquest, ClinicalKey for Nursing, CINAHL and Ovid databases. The published articles from year 2010 onwards are included in this study. Results: A total of 18 articles were analysed in this review. It was found that having good or poor knowledge of diabetes does not guarantee their health-seeking practice of medication adherence. It was also reported that some of the factors that have been found to predict the level of knowledge and their practices include their sociodemographic characteristic. Conclusion: Therefore, the findings of this review giving alarm about future interventions and study in this particular area.